2020
DOI: 10.1108/jwl-09-2019-0112
|View full text |Cite
|
Sign up to set email alerts
|

Practice-based learning and innovation in nursing homes

Abstract: Purpose This paper aims to investigate the conditions under which learning and innovation occur within nursing homes by focusing on how the dynamics of the distribution and transformation of ideas and knowledge may be viewed as a prerequisite for innovation in both formal, planned learning situations and informal, everyday practices. Design/methodology/approach Data was produced via fieldwork, which included participant observations, conversations and research interviews with staff and managers at a Norwegia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
1
25
0
3
Order By: Relevance
“…It also helped the migrant workers to understand the underlying principles of care practices. This approach is consistent with studies demonstrating the need for a supportive learning environment in an increasingly complex sector (Anvik et al., 2020) and for strengthening clinical supervision for foreign educated nurses to increase patient safety competencies (Viken et al., 2018). To create good intergroup communication, equal status in the situation, common goals, inter group cooperation and support from the authorities are essential (Allport, 1954; Munkejord, 2019; Pettigrew & Tropp, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…It also helped the migrant workers to understand the underlying principles of care practices. This approach is consistent with studies demonstrating the need for a supportive learning environment in an increasingly complex sector (Anvik et al., 2020) and for strengthening clinical supervision for foreign educated nurses to increase patient safety competencies (Viken et al., 2018). To create good intergroup communication, equal status in the situation, common goals, inter group cooperation and support from the authorities are essential (Allport, 1954; Munkejord, 2019; Pettigrew & Tropp, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Martinsen stiller spørsmålet: «Er det noe verdt å satse på?» Alvsvåg (2010) svarer at studenten dannes i utdanningen til å formes til en profesjonsutøver. Studentene får mulighet til å laere i et sykehjemsmiljø som er åpent for ideer og nytenking (Anvik, Vedeler, Wegener, Slettebø & Ødegård, 2020). Med dette som bakgrunn hadde vi følgende hensikt med denne studien: å utforske og beskrive hvordan akademia og praksis gjennom samskaping av nytt utdanningsprogram i holistisk personsentrert demensomsorg i et laeringsfellesskap kan bidra til dannelse av sykepleiestudentene på bachelornivå.…”
Section: Dannelse Og Samskapingunclassified
“…For at et laeringsfellesskap mellom akademia og praksis skal oppstå og forbli, trenger akademia å vaere aktiv overfor praksis. En grunn til at samskaping i prosjektet ble erfart som positivt, kan bero på at personalet var en del av et «indre laeringsfellesskap», som samtidig gav rammer for kryssing av grenser (Akkerman & Bakker, 2011;Anvik et al, 2020;Kulla & Slettebø, 2019). Det kan tenkes at laerere/forskere møtes av et «praksisrom» der de må banke på flere ganger, men man kan ikke regne med å ha tilgang til alle «rom» (Martinsen, 2018).…”
Section: Implikasjoner For Forskning Og Akademia-praksislaeringsfelleunclassified
“…[38, 45, 48-50, 53, 55-59] In addition, psychological safety and affordances are facilitators of WBL when staff and students participate together in care situations, such as interprofessional consultation, changing projects, and action research. [46,48,56,60] Conversely, we found that affordances can also be a barrier to individual learning, for instance, when novices are excluded from shift handovers, which are "acknowledged as important opportunities to discuss professional matters in a protected space". [50] In addition, another way of learning collectively with social support in a psychologically safe team, is learning from errors, by sharing knowledge, and reflecting on the process of how errors occurred.…”
Section: Collective Learningmentioning
confidence: 89%